Prevalence of non-adherance and its associated factors of hypertensive patients at Jimma University Specialized Hospital in Southwest Ethiopia - Asmamaw Yenesew; Fanta Gashi; Ramanjireddy Tatiparthi (Indian Journal of Health Sciences and Biomedical Research KLEU, 2015)
Background: Hypertension is an overwhelming disorder worldwide with high morbidity and mortality rates; this may be due to poor adherence. Poor adherence leads to a bad outcome of the disease and increases the more loss of expenditure on resources. Adherence is a methodology of coincidence between the medication advices and patient′s medication management behavior; it includes dosing frequency and time of intake. This study mainly focuses on the prevalence of adherence and its factors affecting on hypertensive patients follow-up at Jimma University Specialized Hospital (JUSH). Methods: It is a hospital-based cross-sectional survey designed with a sample size of 150 subjects. This study is conducted at chronic ambulatory care unit in JUSH from January 24 to February 7, 2014. The collected data were executed for 95% confidence interval between the various demographic levels to identify the significance of the results. Results: The sociodemographic survey of this study showed from the total of 150 respondents, majority of the characteristics were in the categories of sex, female subjects have higher percentage of 56.7% non-adherence significantly, when compared with male subjects, the same significance was observed in age group of 50 years and illiterates of educational level in 63.3% and 50%, respectively. The significant differences were not observed in the characteristics of occupation, area of residence, income, and marital status of the participants. Various factors was analyzed to determine the different reasons behind the non-adherence of hypertensive medication, most of them (120 subjects) reported side effects of hypertensive medications and forgetfulness is one of the major factors, that misses their medication, followed by financial and religious believes. Conclusion and Recommendations: The non-adherence to hypertensive medication was high at JUSH. Hence, the pharmacists and other health care professionals should work in collaboration for escalating the patient′s quality of life. They need to stress the importance of antihypertensive adherence to the patient′s life and the benefits of their medication.